PENGARUH DESAIN LAMAN, PERCEIVED EASE OF USE DAN E-TRUST TERHADAP E-LOYALTY MELALUI E-SATISFACTION SEBAGAI VARIABEL INTERVENING (Studi Pada Konsumen PT Bhineka Rahsa Nusantara) - Laras Dipta Sri Ida Susilowati; I Made Sukresna (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to analyze the effect of information quality on page design, perceived ease of use and e-trust on e-loyalty with e-satisfaction as an intervening variable for PT Bhineka Rahsa Nusantara consumers. Rahsa Nusantara has several sales channels, one of which is a website. Initially, the Rahsa Nusantara website was running well, but as time went on, the number of loyal customers and new customers decreased. However, in 2022 this website will experience a comeback which is the problem in this study to review the effect behind the increase in loyal customer returns. The sample in this study was 200 respondents, namely Rahsa Nusantara customers who had made purchases on the website at least 2 times. The sampling technique used was purposive sampling by distributing questionnaires to the intended respondents. In this study a theoretical model was developed by proposing four hypotheses which would be tested using the Structural Equation Modeling (SEM) tool operated through the AMOS 22.0 program. Based on the results of SEM data processing for models that meet the goodness of fit criteria are as follows chi-square 193.701, significance probability 0.171, CMIN/DF 1.101 RMSEA 0.022, TLI 0.994, CFI 0.995 with one marginal value, namely AGFI value 0.893. With the results obtained, the research model is considered feasible to use. The results of this study indicate that e-loyalty can be increased by improving page design, perceived ease of use and e-trust which can influence e-satisfaction as a determinant of e-loyalty success.